2012
DOI: 10.1002/emmm.201100944
|View full text |Cite
|
Sign up to set email alerts
|

SPRY2 loss enhances ErbB trafficking and PI3K/AKT signalling to drive human and mouse prostate carcinogenesis

Abstract: Loss of SPRY2 and activation of receptor tyrosine kinases are common events in prostate cancer (PC). However, the molecular basis of their interaction and clinical impact remains to be fully examined. SPRY2 loss may functionally synergize with aberrant cellular signalling to drive PC and to promote treatment-resistant disease. Here, we report evidence for a positive feedback regulation of the ErbB-PI3K/AKT cascade by SPRY2 loss in in vitro as well as pre-clinical in vivo models and clinical PC. Reduction in SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 40 publications
(46 reference statements)
5
52
0
Order By: Relevance
“…Consistently, our data also showed that HER2, but not HER3, is involved in the heterodimerization with EGFR and in the regulation of EGF‐induced Akt signaling in HER2‐positive breast cancer cells. In support of our findings, the dominant role of HER2 but not HER3 in the ERK‐dependent EGFR internalization and Akt downregulation was found in prostate cancer and retinal pigment epithelial cells (Gao et al ., 2012; Garay et al ., 2015). These results suggest that the involvement of other members of HER kinase family in the ERK‐dependent feedback downregulation of EGFR and Akt signaling may be context specific (Hendriks et al ., 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, our data also showed that HER2, but not HER3, is involved in the heterodimerization with EGFR and in the regulation of EGF‐induced Akt signaling in HER2‐positive breast cancer cells. In support of our findings, the dominant role of HER2 but not HER3 in the ERK‐dependent EGFR internalization and Akt downregulation was found in prostate cancer and retinal pigment epithelial cells (Gao et al ., 2012; Garay et al ., 2015). These results suggest that the involvement of other members of HER kinase family in the ERK‐dependent feedback downregulation of EGFR and Akt signaling may be context specific (Hendriks et al ., 2003).…”
Section: Discussionmentioning
confidence: 99%
“…15,34,[39][40][41][42][43] Chen et al have demonstrated that the promoter region of spry2 was only hypermethylated in a small fraction of the 55 CLL patients that were profiled, signifying alternate mechanisms that lead to Spry2 downregulation in CLL. 31 Interestingly, we identify SPRY2 as a direct target of miR-21 in human CLL cells.…”
Section: Discussionmentioning
confidence: 99%
“…EGF Stimulation-Upon EGF binding, EGFR is involved in a series of trafficking events, including internalization, degradation, and recycling, which ultimately regulate its signal amplification and propagation (42). Also, integrins are known to regulate the trafficking of some membrane proteins (43).…”
Section: Expression Of Integrin ␣5 Delays Egfr Internalization Uponmentioning
confidence: 99%